ANALISIS KERAPATAN VEGETASI UNTUK AREA PEMUKIMAN DENGAN MEMANFAATAN CITRA SATELIT LANDSAT DI KOTA TASIKMALAYA - miftah Kurnia Hayu; Riki Ridwana (Jurusan Geografi Fakultas Ilmu Sosial Universitas Negeri Padang, 2019)
Global warming is an important issue to discuss because it is very impactful to human life, one of the factors influencing increase global warming is decreasing the green vegetation continuously that exist in both urban and rural areas. Especially in urban areas because it is the center of human activity. The high level of human activity centered in the city leads to an increase in the need for land use which will lead to reduced vegetation density levels. Utilization of remote sensing images can be used to determine the density of vegetation in an area. Vegetation density analysis can be done by means of digital imagery intrepetation using the transformation of NDVI (Normalized Different Vegetation Index). The purpose of this research is to know the land use through the calculation of vegetation index of residential area in Tasikmalaya city.